2014
DOI: 10.1016/j.avb.2014.05.004
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of primary prevention strategies for sexual violence perpetration

Abstract: This systematic review examined 140 outcome evaluations of primary prevention strategies for sexual violence perpetration. The review had two goals: 1) to describe and assess the breadth, quality, and evolution of evaluation research in this area; and 2) to summarize the best available research evidence for sexual violence prevention practitioners by categorizing programs with regard to their evidence of effectiveness on sexual violence behavioral outcomes in a rigorous evaluation. The majority of sexual viole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
573
2
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 626 publications
(644 citation statements)
references
References 82 publications
(135 reference statements)
14
573
2
10
Order By: Relevance
“…Current approaches include aggressive education about sexual violence that seeks to change attitudes, knowledge, and culture, but evidence to identify best practices that reduce sexual violence perpetration is minimal. 137,138 A recent Cochrane review examined 38 studies of educational or skillsbased interventions for preventing relationship and dating violence in adolescents and young adults. The results showed no evidence that the programs enhanced skills to prevent relationship violence or decreased relationship violence.…”
Section: Sexual Assault Preventionmentioning
confidence: 99%
“…Current approaches include aggressive education about sexual violence that seeks to change attitudes, knowledge, and culture, but evidence to identify best practices that reduce sexual violence perpetration is minimal. 137,138 A recent Cochrane review examined 38 studies of educational or skillsbased interventions for preventing relationship and dating violence in adolescents and young adults. The results showed no evidence that the programs enhanced skills to prevent relationship violence or decreased relationship violence.…”
Section: Sexual Assault Preventionmentioning
confidence: 99%
“…One of the most robust evaluations of interventions in the criminal justice system is that of Boba and Lilley (2009) concerning the consequences of the Violence Against Women Act 1994 funding (DeGue et al, 2014). This showed that the US$1.6 billion federal funding had a demonstrable effect in reducing the rate of rape, largely due to improved law enforcement.…”
Section: Ways Forwardmentioning
confidence: 99%
“…The WHO (2014b, p 77) find that 'few programmes have been rigorously evaluated.' In a systematic review of strategies to prevent sexual violence perpetration, DeGue et al (2014) found that the majority of the interventions noted in the 140 outcome evaluation studies reviewed were brief psycho-educational programmes focused on increasing knowledge or changing attitudes, none of which had been shown to be effective when a rigorous 'public health' method of evaluation was used. The US Centers for Disease Control and Prevention (Breiding et al, 2014) finds that little is known about what works to prevent sexual violence, noting that only one programme had been shown to prevent sexual violence perpetration.…”
Section: Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years there has been a growing movement towards a more comprehensive public health understanding and response to sexual violence, focusing on the importance of prevention efforts (Casey & Lindhorst, 2009;DeGue et al, 2014;Lee et al, 2007;Nation et al, 2003;Tabachnick and Klein, 2011). As awareness of and interest in prevention efforts increase, the public has become more engaged and asking for more accurate information about those who abuse, supporting the need for programs that prevent the perpetration of sexual abuse.…”
Section: Practical Applications Of Perpetration Prevention Strategiesmentioning
confidence: 99%